A stability analysis on forced convection boundary layer stagnation-point slip flow in Darcy-Forchheimer porous medium towards a shrinking sheet - Abu Bakar, Shahirah; Md. Arifin, Norihan; Md. Ali, Fadzilah; Bachok @ Lati, Norfifah; Mohd Nazar, Roslinda (AIP Publishing, 2016)
The stagnation-point flow over a shrinking sheet in Darcy-Forchheimer porous medium is numerically studied. The governing partial differential equations are transformed into ordinary differential equations using a similarity transformation, and then solved numerically by using shooting technique method with Maple implementation. Dual solutions are observed in a certain range of the shrinking parameter. Regarding on numerical solutions, we prepared stability analysis to identify which solution is stable between non-unique solutions by bvp4c solver in Matlab. Further we obtain numerical results or each solution, which enable us to discuss the features of the respective solutions.